2011
DOI: 10.1186/1743-422x-8-457
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of polio to its eradication in Pakistan

Abstract: BackgroundThis study is based on EPI (Expanded Program on Immunization) immunization surveys and surveillance of polio, its challenges in immunization and the way forward to overcome these challenges.MethodsSeveral Government documents, survey reports and unpublished program documents were studied and online search was made to find information on EPI Pakistan. SPSS 16 and Microsoft Excel 2007 were used for the statistical analysis.ResultsImmunization against polio is higher in urban areas as compared to rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 3 publications
3
30
0
Order By: Relevance
“…These include inconsistent quality of SIAs; failure to immunize children in many areas; inaccessibility of children due to ongoing military conflict; massive floods; poor routine immunization services; a structurally weak polio eradication programme; large nomadic and internally-displaced populations, and the refusal of some parents to have their children vaccinated. 9,10 Many of these factors have led to the clustering of unimmunized children, who are at high risk of getting polio. 11 Very few studies evaluating the results of polio SIAs in Karachi have been published.…”
Section: Introductionmentioning
confidence: 99%
“…These include inconsistent quality of SIAs; failure to immunize children in many areas; inaccessibility of children due to ongoing military conflict; massive floods; poor routine immunization services; a structurally weak polio eradication programme; large nomadic and internally-displaced populations, and the refusal of some parents to have their children vaccinated. 9,10 Many of these factors have led to the clustering of unimmunized children, who are at high risk of getting polio. 11 Very few studies evaluating the results of polio SIAs in Karachi have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Also of concern is the knowledge that in similar eradication efforts, such as polio and guinea worm, disease incidence has fallen steeply during the early stages of the campaign but then leveled off due to nonlinear effects [4][5][6]. For example, malaria may be easily controlled in accessible, economically stronger regions, but remain refractory in remote, poorly resourced areas such as border regions where the per capita expenditure required for elimination surges.…”
mentioning
confidence: 99%
“…Shortage of skilled staffs at health facilities need to be addressed by recruiting more staffs to involve in the routine immunization program so that EPI coverage significantly improves. This recommendation was in line with the problem identified previously as the inadequate service delivery, lack of information about immunization and inadequate number of vaccinators were found to be one of the main reasons for the poor performance and large number of polio cases reported each year [16]. Similarly, it is was pointed out that WHO need to hire more Polio Eradication Officers to the uncovered districts of the province in order to effectively support SIAs and surveillance activities.…”
Section: Experts' Recommendationmentioning
confidence: 56%
“…Despite the high coverage administrative report for fully immunized children, surveys conducted from 1995 to 2007 for immunization in Pakistan, indicated that only about half of the targeted children were fully immunized [16]. Because of the high dropout rate, a very low proportion of children fully complete DPT3(Diphtheria, Pertussis and Tetanus 3rd Vaccine) [17].…”
mentioning
confidence: 99%